Awareness of Stakeholders about Inclusive Education - Berwal, Sandeep; Tehlan Dahiya, Varuna (Revija za elementarno izobraževanje, 2025)
This paper examines the level of awareness among stakeholders about inclusive education. The sample comprises thirty school heads, 108 class teachers, forty-four parents, and twenty-eight School Management Committee members. A thirty-item self-constructed awareness questionnaire was administered for data collection, and the data was analysed using descriptive statistics. Findings indicate that stakeholders are highly aware of inclusive education and that parents are the most aware among all categories of stakeholders. In terms of gender, female stakeholders proved to be more aware than their male counterparts. An influence of educational qualifications on awareness level is visible since stakeholders with a higher level of education demonstrated higher levels of awareness.
Keywords: awareness, Inclusive Education, Stakeholders.